Cyclodextrin-templated porphyrin nanorings - Liu, P; Neuhaus, P; Kondratuk, D; Balaban, T; Anderson, H (Wiley, 2014)
α- and β-Cyclodextrins have been used as scaffolds for the synthesis of six- and seven-legged templates by functionalizing every primary CH2OH with a 4-pyridyl moiety. Although these templates are flexible, they are very effective for directing the synthesis of macrocyclic porphyrin oligomers consisting of six or seven porphyrin units. The transfer of chirality from the cyclodextrin templates to their nanoring hosts is evident from NMR and circular dichroism spectroscopy. Surprisingly, the mean effective molarity for binding the flexible α-cyclodextrin-based template within the six-porphyrin nanoring (74 M) is almost as high as for the previously studied rigid hexadentate template (180 M). The discovery that flexible templates are effective in this system, and the availability of a template with a prime number of binding sites, open up many possibilities for the template-directed synthesis of larger macrocycles. Floppy yet effective: Cyclodextrins have been decorated with pyridine legs to create chiral templates for directing the synthesis of nanorings consisting of six or seven zinc porphyrin macrocycles. The flexibility of these cyclodextrin derivatives does not make them less effective as templates, and it only slightly reduces the cooperativity of their interactions with the nanorings. © 2014 The Authors. Published by Wiley-VCH Verlag GmbH and Co. KGaA. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.